Upaya Penyeimbangan Beban Kerja Karyawan dengan Pendekatan Full Time Equivalent (FTE) di PT X - Regasia Singkali; I Nyoman Sutapa (Jurnal Titra, 2021)
PT X is a shipping and logistic company that has been operating since 1970 in Surabaya City. One of the divisions in PT X is Division Y. The problem of Division Y is the workload imbalance between employees in one department. This research aims to measure the employee workload condition and provide suggestions to improve the workload balance among employees. This research uses the Full Time Equivalent (FTE) method, where the employee’s total workload will be compared to the total effective working time available. The results of measuring the six department workload of Division Y show that 25,7% of employees is underload, 62,8% of employees have a normal workload, and 11,4% of employees is overload. The workload improvements that carried out are proposing additional job to the underload employees, shifting job between employees, and updating the information system program. These improvements were able to improve the employee workload balance to 11% of underload employees, 86% of normal load employees, and 3% of overload employees.